Kekerasan dalam Agama dan atas Nama Agama: Fenomena Idiologi Keagamaan berbasis Radikalisme dan Terorisme di Indonesia - Madnur, Madnur (Program Pascasarjana IAIN Langsa, 2023)
This paper examines violence within religion and in the name of religion and how it relates to the phenomena of acts of violence, radicalism, and terrorism that have occurred in Indonesia. Religious teachings with nuances of violence are always an excuse for taking actions outside of spiritual and human reason. This causes the good values in religion, which are considered sacred, to be tarnished and even becomes a turning point for the religion itself. Acts of violence, radicalism, and terrorism that have occurred in Indonesia are mainly due to the motivation of religious understanding carried out by certain ideological groups that tend to understand harsh and extreme religions. This paper uses the literary method taken from several journals, dissertations, books, and other scientific articles related to the theme of this research.